La influencia de los derechos humanos en la jurisprudencia cautelar de la CIJ : reescribiendo los límites de la protección - Elías, Víctor Lisandro (2015)
Within its powers, the International Court of Justice has the ability to order provisional measures to preserve the rights subject to litigation. However, case law demonstrates the issuing of provisional measures in respect of situations not under its jurisdiction when human rights are at stake. Such position can be considered as an illegitimate expansion of its jurisdiction or as the exercise of the judicial function inherent powers. In this dichotomy human rights play a key role and have made the difference, redefining the scope of the interim competence.